PEMBERDAYAAN SAMPAH PLASTIK TUTUPAN BOTOL UNTUK DIJADIKAN MEJA DENGAN ALAS ECOBRICK DI DESA MELER - Ramadhan Ramadhan; Fersianus Jula; Selestina Vinitri Nagoya; Stefanus Naru; Yohanes Dionesius Ukut; Makrina Putriana Banut; Hardianus Arson (FKIP Universitas Trilogi, 2025)
This study aims to empower the community of Meler Village in managing plastic waste, particularly bottle caps, by transforming it into a functional product in the form of a table with an ecobrick-based foundation. Bottle caps represent a small-sized plastic waste category that is difficult to decompose and has the potential to become a significant source of microplastics in the environment. Using a qualitative descriptive approach, the program was carried out through community outreach, ecobrick making training, and practical activities in arranging bottle caps as the table surface. Data were collected through observations and documentation throughout the implementation process. The results show that the community successfully produced one eco-friendly table, featuring a top surface composed of plastic bottle caps and a base supported by ecobricks. The product demonstrates not only aesthetic value and structural strength but also environmental benefits by reducing plastic waste. This empowerment initiative has enhanced community awareness, skills, and participation in recycling-based waste management and has the potential to serve as a sustainable waste management model at the village level.